2019
DOI: 10.1002/pon.5083
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, correlates of depression, and its impact on quality of life of cancer patients attending a palliative care setting in South India

Abstract: Objective Depression is an easily treatable yet frequently underdiagnosed affliction in palliative population with deleterious implications on their quality of life. It has been studied poorly in developing countries like India. Methods A cross‐sectional study was done with 234 consenting subjects attending a palliative care unit. Patient Health Questionnaire‐9 (PHQ‐9), World Health Organization Quality of Life (WHOQOL‐BREF), and semi‐structured proforma were used by trained nonmental health professional to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…It is understandable that an inability to pay the cost of treatment acted as a key cause of emotional distress. Several studies have also highlighted the important role of financial difficulties in the development of emotional problems in cancer patients (18,19). Thus, measurements in the present study were taken to ensure that the rate of underdiagnosed psychiatric morbidities was reduced, especially for patients that are financially-burdened.…”
Section: Discussionmentioning
confidence: 99%
“…It is understandable that an inability to pay the cost of treatment acted as a key cause of emotional distress. Several studies have also highlighted the important role of financial difficulties in the development of emotional problems in cancer patients (18,19). Thus, measurements in the present study were taken to ensure that the rate of underdiagnosed psychiatric morbidities was reduced, especially for patients that are financially-burdened.…”
Section: Discussionmentioning
confidence: 99%
“…Simply being able to go out from their bed or their home was a source of relief (Aebischer et al, 2018; Pareek et al, 2019). A cross-sectional study on 234 individuals with advanced stages of cancer, who attended palliative care in South India, reported prevalence major depression (70%) among patients (Sudarisan et al, 2019). Sudarisan reported that the presence of financial difficulties (3.9; 95% Cl, 2.00–7.61) and the absence of health insurance (OR = 1.92, 95% Cl, 1.02–3.7) were significantly associated with major depression (Sudarisan et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Simply being able to go out from their bed or their home was a source of relief (Aebischer et al, 2018;Pareek et al, 2019). A cross-sectional study on 234 individuals with advanced stages of cancer, who attended palliative care in South India, reported prevalence major depression (70%) among patients (Sudarisan et al, 2019).…”
Section: Psycho-social Challenges and Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychological conditions such as depression can greatly affect the progression of the disease. [ 13 ] Many cancer patients as well as physicians believe that the patient's mental state can affect the outcome of treatment. [ 14 ] Cancer patients with depression have a higher mortality prevalence than nondepressed patients, which highlights the importance of preventing and treating depression in these patients.…”
Section: Introductionmentioning
confidence: 99%